Genome-wide association study identified candidate genes controlling continuous storage root formation and bulking in hexaploid sweetpotato - Bararyenya, A.; Olukolu, B.A.; Tukamuhabwe, Phineas; Grüneberg, W.J.; Ekaya, Wellington N.; Ochwo-Ssemakula, Mildred; Odong, Thomas L.; Talwana, Herbert A.L.; Badji, Arfang; Kyallo, Martina M.; Gemenet, D.; Kitavi, M.; et al. (Springer, 2020)
Candidate genes identified in this study have potential roles in cell wall remodeling, plant growth, senescence, stress, root development and redox signaling. These findings provide valuable insights into understanding the functional networks to develop strategies for sweetpotato yield improvement. The markers as well as candidate genes identified in this pioneering research for CSRFAB provide important genomic resources for sweetpotato and other root crops.